2020
DOI: 10.3390/ma13051071
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Adding MoDTC on the Properties of Carbon Black Rubber and the Friction and Wear of Metal during Mixing Process

Abstract: The gap between the rotor and the mixer chamber wall is an important factor in determining filler dispersion in rubber compounds. The inner wall of a mixer will wear after working for a long time, which will cause poor filler dispersion and affect the quality of rubber products. In this study, MoDTC was added to carbon black as a kind of filler, and the effect on filler dispersion, the properties of the rubber product, and the friction and wear of rubber and metal in the mixing process were examined. Experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…It is known that the beneficial effect of this class of organo-molybdenum compounds resides in the possibility to generate layers of molybdenum disulfide (MoS 2 ) in tribological conditions . Recent works regarding MoDTC complexes have demonstrated their capability to reduce friction also at metal/diamond-like–carbon and metal/rubber contacts, and promising applications have been described in combination with textured metallic surfaces and nanoparticles. , While wide experimental research has been carried out to describe the chemical and tribological behavior of MoDTC in engine oils and its interaction with ZnDTP, little attention has been paid to the fundamental steps of the tribochemical reaction that forms the beneficial MoS 2 tribolayers. The first elementary step of this reaction is the dissociation of the molecule into two separate fragments.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that the beneficial effect of this class of organo-molybdenum compounds resides in the possibility to generate layers of molybdenum disulfide (MoS 2 ) in tribological conditions . Recent works regarding MoDTC complexes have demonstrated their capability to reduce friction also at metal/diamond-like–carbon and metal/rubber contacts, and promising applications have been described in combination with textured metallic surfaces and nanoparticles. , While wide experimental research has been carried out to describe the chemical and tribological behavior of MoDTC in engine oils and its interaction with ZnDTP, little attention has been paid to the fundamental steps of the tribochemical reaction that forms the beneficial MoS 2 tribolayers. The first elementary step of this reaction is the dissociation of the molecule into two separate fragments.…”
Section: Introductionmentioning
confidence: 99%
“…The rolling friction coefficient increases with the acceleration of speed, and as the intensity of the magnetic field increases, the rolling friction coefficient also increases to a certain extent. As metal-rubber [22,23] is a common friction pair in the industry, the copper ball-MRE is selected as the friction pair to explore the influence of the magnetic field on the rolling friction coefficient in dry and wet environments. The rolling friction coefficients of the copper balls as friction pairs under different magnetic fields are shown in Figure 4a.…”
Section: Resultsmentioning
confidence: 99%
“…Kaushik Pal [6] studied the effect of fillers on the rubber's alloy morphology and wear characteristics. Accordingly, it was found that ISAF N234 significantly improves the tire's curing, mechanical, and thermal characteristics.…”
Section: Introductionmentioning
confidence: 99%